Hydrogen Sulfide Relaxes Human Uterine Artery via Activating Smooth Muscle BKCa Channels - Yan Li; Jin Bai; Yi-hua Yang; Naoto Hoshi; Dong-bao Chen (MDPI AG, 2020)
Opening of large conductance calcium-activated and voltage-dependent potassium (BKCa) channels hyperpolarizes plasma membranes of smooth muscle (SM) to cause vasodilation, underling a key mechanism for mediating uterine artery (UA) dilation in pregnancy. Hydrogen sulfide (H2S) has been recently identified as a new UA vasodilator, yet the mechanism underlying H2S-induced UA dilation is unknown. Here, we tested whether H2S activated BKCa channels in human UA smooth muscle cells (hUASMC) to mediate UA relaxation. Multiple BKCa subunits were found in human UA in vitro and hUASMC in vitro, and high β1 and γ1 proteins were localized in SM cells in human UA. Baseline outward currents, recorded by whole-cell and single-channel patch clamps, were significantly inhibited by specific BKCa blockers iberiotoxin (IBTX) or tetraethylammonium, showing specific BKCa activity in hUASMC. H2S dose (NaHS, 1-1000 µM)-dependently potentiated BKCa currents and open probability. Co-incubation with a Ca2+ blocker nifedipine (5 µM) or a chelator (ethylene glycol-bis (β-aminoethyl ether)-N,N,N',N'-tetraacetic acid (EGTA), 5 mM) did not alter H2S-potentiated BKCa currents and open probability. NaHS also dose-dependently relaxed phenylephrine pre-constricted freshly prepared human UA rings, which was inhibited by IBTX. Thus, H2S stimulated human UA relaxation at least partially via activating SM BKCa channels independent of extracellular Ca2+.